Negotiated identity of teachers of English as a foreign language (EFL): A sociocultural perspective - Abdel Fattah, Nesma Hossam Eldin (AUC Knowledge Fountain, 2016)
Many studies have investigated the sociocultural aspects of professional identities of EFL teachers in different contexts. However, a limited amount of research has been conducted on the negotiation of teachers’ identities particularly in the Arab world and in Egypt. The current study investigates the factors that contribute to forming and negotiating the sociocultural aspects of the professional identity of six experienced and six novice Egyptian teachers of English as a second language (EFL). The study is conducted in two English language programs, one in a private university and the other in a public university context. Interviews and classroom observations were conducted with all twelve teachers. A framework is introduced to conceptualize the negotiation of a professional identity construct that is associated with a number of social and cultural factors, including past teaching and non-teaching professional experiences which influence identity development and shared identity formation. Tajfel’s (1982) theory of social identity was found to reflect a level of the teachers’ professional identities along with the sense of the teachers’ shared identities. Experience, in addition to other external factors such as context, institution and culture, appeared to be one of the variables affecting the negotiation of the sociocultural aspects of teachers’ professional identities both in their self-reported data and classroom practices. The study suggests some pedagogical implications that if emphasized in teacher education programs could assist teachers in negotiating their professional identities in accordance with the surrounding sociocultural factors of different contexts.